CURRENT CONCEPTS IN SPONDYLOSIS PATHOGENESIS, CLINICAL MANIFESTATIONS, DIAGNOSIS AND EVIDENCE-BASED MANAGEMENT - Hasanova Zaynura (International Journal of Literature and Language Studies, 2026)
This article discusses the definition of spondylosis, its causes, pathophysiological mechanisms, and age-related degenerative changes affecting the vertebral column. It examines the clinical manifestations of cervical and lumbar spondylosis, including radiculopathy, myelopathy, spinal stenosis, and neurogenic claudication. The article also highlights the diagnostic methods, physical examination findings, and imaging criteria used to identify the disease. Furthermore, conservative treatment strategies, physical therapy, pain management, and current surgical approaches for cervical and lumbar spondylosis are reviewed and discussed.